2016
DOI: 10.1016/j.conbuildmat.2016.06.114
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance and cost analysis of mortars made with PCM and different binders

Abstract: h i g h l i g h t s PCM mortars based in different binders were used to study the thermal behavior. The thermal behavior and cost analyses were evaluated based in Portuguese climate. The PCM mortars reveal higher thermal regulation and lower energy needs. The PCM mortars showed a decrease of the cost related to the energy consumption. a b s t r a c tThe high energetic consumption is one of the biggest concerns of modern society. The incorporation of phase change materials (PCM) in construction materials allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Another point that needs to be emphasized is the determination of the optimum PCM ratio to be used in the construction. In this study, it was observed that as the amount of PCM used increases, the thermal performance of the material increases in accordance with the studies in the literature . It can easily be said that when the amount of PCM is increased, the latent heat capacity of the mixtures increases and thermal conductivity decreases.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another point that needs to be emphasized is the determination of the optimum PCM ratio to be used in the construction. In this study, it was observed that as the amount of PCM used increases, the thermal performance of the material increases in accordance with the studies in the literature . It can easily be said that when the amount of PCM is increased, the latent heat capacity of the mixtures increases and thermal conductivity decreases.…”
Section: Discussionsupporting
confidence: 87%
“…Cunha et al . tested the thermal and mechanical performance of mortars made with PCM and different binders. They also conducted cost analysis based on energy consumption of mortars and energy price in Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…Type K thermocouples were used. The described set-up is able to supply important and reliable information on the thermal behavior of the mortars, as previously demonstrated [34,35].…”
Section: Methodsmentioning
confidence: 75%
“…Type K thermocouples were used. The described set-up is able to supply important and reliable information on the thermal behavior of the mortars, as previously demonstrated [34,35]. The thermal behavior of the produced mortars was tested in a climatic chamber, setting a temperature program representative of each season of the year, in order to study the thermal behavior of the developed mortars in summer, spring, autumn and winter.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation